2019
DOI: 10.5014/ajot.2020.033456
|View full text |Cite
|
Sign up to set email alerts
|

Play in Children With Life-Threatening and Life-Limiting Conditions: A Scoping Review

Abstract: Unfortunately, little attention has been paid to the need for play in children living with life-threatening and life-limiting conditions (LTC/LLC; Amery, 2016; Boucher et al., 2014). The number of children diagnosed with LTC/LLC worldwide is estimated to be more than 21 million (Connor et al., 2017). These children often experience loss or impairment that affects their participation in play, but the role and value of play may be even greater for vulnerable children with LTC/ LLC than for healthy children (Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…Play is an essential determinant of children's health; a strong positive relationship exists between participation in play and children's health and well‐being (Gerlach et al, 2014; Law & King, 2014; Moore & Lynch, 2018). However, play is under‐researched for children living with life threatening/limiting conditions, despite the fact that these children are experiencing sustained disruption in their play (Jasem et al, 2020). Life threatening/limiting conditions are mainly characterized with shortened lifespan, where the likelihood of death is before reaching adulthood (i.e., before their 18th birthday) (McNamara‐Goodger & Feudtner, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Play is an essential determinant of children's health; a strong positive relationship exists between participation in play and children's health and well‐being (Gerlach et al, 2014; Law & King, 2014; Moore & Lynch, 2018). However, play is under‐researched for children living with life threatening/limiting conditions, despite the fact that these children are experiencing sustained disruption in their play (Jasem et al, 2020). Life threatening/limiting conditions are mainly characterized with shortened lifespan, where the likelihood of death is before reaching adulthood (i.e., before their 18th birthday) (McNamara‐Goodger & Feudtner, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They can benefit from the process of engagement (i.e., interaction with peers allows children to fully experience their childhood) and from participation (i.e., developing later‐life skills) (Lynch & Moore, 2016; Mandich & Rodger, 2006; Sturgess, 2003). The few available studies have indicated that a hospital stay (or hospitalization) restricts play for children who are living with life threatening/limiting conditions (Angstrom‐Brannstrom et al, 2013; Jasem et al, 2020; Lima & Santos, 2015). It has been shown that children are often unable to engage in many of their desired play activities, such as building Lego or colouring and reading, because of hospitalization (Angstrom‐Brannstrom et al, 2013; Gibson et al, 2010; Lambert et al, 2014b; Lima & Santos, 2015; Nabors et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations